Integrating Artificial Intelligence in Education: : Trends and Opportunities - Wangdi, Pema (Universitas Terbuka, 2024)
Artificial Intelligence (AI) is transforming educational practices by facilitating personalized learning, automating grading processes, and enhancing support through intelligent tutoring systems. This systematic review explores AI's integration in educational settings, highlighting its contributions to increased productivity and tailored learning experiences. It addresses key challenges including data privacy, algorithmic bias, and the need for enhanced accountability and transparency in AI applications. The review also discusses strategic recommendations for embedding ethical AI into curriculum design and emphasizes the importance of professional development for educators. Collaboration among educational stakeholders is vital for advancing responsible AI utilization. By synthesizing recent literature, this review provides insights into AI tools' effectiveness, explores ethical dimensions of technology in classrooms, and suggests future directions for research and practice in educational AI. This analysis serves as a resource for educators, policymakers, and technologists aiming to optimize AI benefits in education.